2021
DOI: 10.20535/2617-9741.1.2021.228137
|View full text |Cite
|
Sign up to set email alerts
|

The phenomenon of conservative-perturbed equilibrium in conditions different reactors

Abstract: Finding the optimal mode is a conceptual problem. The most important indicator that reflects the perfection of a chemical reactor is the intensity of the process in it. The phenomenon of conservatively perturbed-equilibrium (CPE) in the conditions of different types of reactors (in acyclic and cyclic systems) was studied: the ideal displacement reactor ("steady-state plug flow reactor, PFR") and the ideal mixing reactor ("steady-state continuous stirred tank reactor, CSTR"). For the acyclic reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…where L CPE is the length at which the extremum of the chosen component is reached and L eq is the reactor length at which the molar flow rate of this component is located within the vicinity of its equilibrium value (±2.5%) Corresponding results for different cases are shown in Table 4. The majority of previous studies of the CPE phenomenon were performed using only linear models for better analytical understanding [2,3,5,6]. This study, on the contrary, uses non-linear real-world kinetic models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…where L CPE is the length at which the extremum of the chosen component is reached and L eq is the reactor length at which the molar flow rate of this component is located within the vicinity of its equilibrium value (±2.5%) Corresponding results for different cases are shown in Table 4. The majority of previous studies of the CPE phenomenon were performed using only linear models for better analytical understanding [2,3,5,6]. This study, on the contrary, uses non-linear real-world kinetic models.…”
Section: Discussionmentioning
confidence: 99%
“…This is an important feature of the CPE regime, which can be used for intensifying catalytic processes. In many calculations [5,6], it is shown that in some domain, the magnitude of this extremum is proportional to the perturbation of initial concentration, i.e., CPE is the unavoidable and controlled phenomenon.…”
Section: Unperturbed Speciesmentioning
confidence: 99%
See 1 more Smart Citation